Capital punishment for drug offenders in Malaysia: balancing between human rights and utilitarian rationales / Aizuddin Sapian ... [et al.] - Sapian, Aizuddin; Abdul Manaf, Azman; Zainal Abidin, Siti Aisyah; Mustafa, Nurmifatul Shuhadah (2009)
Many countries in Asia, including Malaysia, impose the death penalty for nonviolent crimes, including drug related crimes. Capital punishment is irrevocable and can be inflicted on the innocent. It has never been shown to deter crime more effectively than other punishments. Every death sentence is an affront to human dignity, every execution a symptom of, not a solution to, a culture of violence. However, the government holds a different view. It reserves the death penalty for those who carry, say, above fifteen grammes of heroin because of the harm that they would have had on the populace, if the drug had been disseminated. This reservation strengthens the government's stand on the import of dangerous quantities of drugs. It is a message to the drug offenders, who would always attempt to maximise their profits by carrying more drugs on each trip, not to entertain such ideas. It is prevention within deterrence, minimising the damage. It is a sort of damage control.